Nowe zjawiska we wzajemnych zależnościach między WTO, Unią Europejską i Polską w polityce rolnej - Puślecki, Zdzisław W. (WYDAWNICTWO NAUKOWE UNIWERSYTETU IM. ADAMA MICKIEWICZA, POZNAŃ, 2011)
The aim of the paper was to present new phenomena in mutual relationships between WTO, the European Union and Poland in terms of agricultural policy. In view of the CAP operation it is essential to adapt its mechanisms to new conditions for the development of world economy. The source of failure of the Doha round stemmed from the difference in opinions between the USA and the EU concerning a reduction of subsidies in agriculture, which was also connected with the determined position of developing countries on a reduction of subsidizing of agriculture by developed countries. In the future as a result of necessary reforms, WTO should continue to stimulate liberalisation of international trade as well as increase support for the development of the Third World countries. Changes introduced to the Common Agricultural Policy, also under the influence of WTO, are of paramount importance for Poland. These changes have to be reflected in the strategy of Poland during negotiations on the EU budget.

Lo scopo è di presentare i nuovi sviluppi nel rapporto di reciproca dipendenza tra l’OMC, l’Unione europea e la Polonia nella politica agricola. Nella prospettiva del funzionamento della PAC, è essenziale l’esigenza di adeguare i suoi meccanismi alle nuove condizioni dello sviluppo dell'economia mondiale. Alla base del fallimento del Doha Round erano le differenze di opinione tra Stati Uniti e Unione europea concernenti la riduzione del livello delle sovvenzioni in agricoltura, il che era anche legato ad una ferma posizione dei paesi in via di sviluppo riguardo alla riduzione dei sussidi agricoli da parte dei paesi fortemente sviluppati. In futuro, a seguito delle necessarie riforme, l’OMC dovrebbe continuare a favorire la liberalizzazione del commercio internazionale e, più che fino ad ora, il sostegno allo sviluppo dei paesi del Terzo Mondo. Effettuati, anche sotto l’influenza della WTO, i cambiamenti nella Politica Agricola Comune sono di grande importanza per la Polonia. Le modifiche in questione devono trovare l’espressione nella strategia della Polonia nell’ambito dei negoziati sul bilancio dell’Unione europea.
NEW PHENOMENA IN MUTUAL RELATIONSHIPS BETWEEN WTO, THE EUROPEAN UNION AND POLAND IN AGRICULTURAL POLICY
NUOVI FENOMENI NEL RAPPORTO DI RECIPROCA DIPENDENZA TRA L’OMC, L’UNIONE EUROPEA E LA POLONIA NELLA POLITICA AGRICOLA